Novel fabrication of marizomib-loaded chitosan-coated hydroxyapatite nanocarriers as a promising system for effective treatment of ovarian cancer - Jia Xu; Meimei Liao; Yi Chen; Lingfeng Chen (Materials Research Express, 2022)
Cancer therapy might benefit significantly from nanotechnology. These nano-drug delivery systems (NDDS) have been established to improve the therapeutic benefits of anticancer medications by enhancing their bioavailability, degradation, and biocompatibility. One of the most promising NDDS for cancer therapy is high-performance hydroxyapatite (HA) nanoparticles, which have many advantages. The metabolite marizomib inhibits tumor cell growth and progression, functioning as a biochemical inhibitor in many malignancies. However, this substance’s low bioavailability is the most significant problem with its use. In this work, a pH-sensitive biopolymer was employed to encapsulate HA nanoparticles with chitosan to increase marizomib’s (MARI) efficacy and bioavailability. The sol-gel process was used to fabricate HA nanoparticles for this purpose. It was then coated with chitosan before encasing the marizomib drug in the nanocarrier, which was done under controlled circumstances. The newly fabricated nanoparticles effectively kill ovarian A2780 cancer cells and induce apoptosis. The morphological examination of the cancer cells was examined by AO/EB and DAPI staining methods. Further, the cell uptake was measured by the flow cytometry methods, and the result shows the nanoparticles were effectively uptake the cancer cells under different incubation times. In principle, nanoparticles have great potential for future pre-clinical applications in treating ovarian cancer cells and suppressing other types of tumors.